2021
DOI: 10.1088/1361-6595/abe6e5
|View full text |Cite
|
Sign up to set email alerts
|

Energy relaxation and heating in the afterglow of high electric field ns-discharges in ambient air using spontaneous Raman scattering

Abstract: The spatio-temporal rovibrational excitation and relaxation mechanisms of N2(X) in the post-discarge of a 10 ns high-voltage diffuse discharge are studied by Spontaneous Raman Scattering. It is shown that the vibrational excitation of nitrogen molecules remains high despite the strong electric fields applied during the discharge itself and the relaxation processes are similar to lower voltage ns discharges. The main differences with the lower field discharges are rather visible at the beginning of the discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…As reported in [55], the O ground states density can be as high as 20% of the initial O 2 density at 1.5 mm from the pin in the early post-discharge. Due to the high electric fields measured up to 6 ns in the pin region [7], the O 2 dissociation rate can be expected to be much higher closer to the pin.…”
Section: Annexesupporting
confidence: 64%
See 1 more Smart Citation
“…As reported in [55], the O ground states density can be as high as 20% of the initial O 2 density at 1.5 mm from the pin in the early post-discharge. Due to the high electric fields measured up to 6 ns in the pin region [7], the O 2 dissociation rate can be expected to be much higher closer to the pin.…”
Section: Annexesupporting
confidence: 64%
“…With R2 equal to 19.43, the final expression of ∆λ VdW is given in table A1 as a function of pressure and gas temperature. In the first hundred of nanoseconds of the discharge dynamics, the increase of the temperature which is observed near the pin is so fast that it can be considered as isochore [29,55]. T g reaches 450 K at 8 ns within the first 500 µm from the pin, which corresponds to a pressure of 1.54 bar.…”
Section: Annexementioning
confidence: 99%
“…Those results show that the water vapor addition can enhance the heating processes in a few nanoseconds in the high field region of the pin but not in the areas where the field is lower. The gas temperature during the early postdischarge has been also obtained by spontaneous Raman scattering [55]. Those measurements showed that the temperature spatial mapping in the first 300 ns of the post-discharge suggests that 1 ± 0.4 mJ is spent in fast heating at the pin in dry air and 1.5 ± 0.4 mJ in humid air.…”
Section: Figure 10 Time Evolution Of the Gas Temperature In Dry And Humid Air (72% Rh) At 85 Kv Three Locations Along The Gap (Pin Mid-gamentioning
confidence: 99%
“…At these conditions, efficient vibrational excitation is produced by electron impact, over a wide range of reduced electric fields (E/N). Strong vibrational excitation of N 2 has also been detected in ns pulse discharges in nitrogen and air [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 88%